The impact of internet pornography addiction on brain function: a functional near-infrared spectroscopy study - Shu, Qicheng; Tang, Shiyu; Wu, Zhenhua; Feng, Jiahuan; Lv, Wenhao; Huang, Min; Xu, Fan (Frontiers in Human Neuroscience, 2025)
IntroductionThere is extensive awareness of internet pornography addiction. It not only affects the mental health of adolescents but also promotes criminal activity. However, the impact of internet pornography addiction on functional in the brain remains unclear.Methods16 healthy college students and five college students with severe internet pornography addiction were invited to participate in the experiment and watch a pornographic video. Functional near-infrared spectroscopy (fNIRS) was used to measure the dynamic changes in hemoglobin in the brain during a 10 min session of viewing internet pornography. Participants completed the Stroop Color and Word Task (SCWT) before and after they had watched the video. Facial expressions and life signs were measured continuously during the experiment.ResultsCompared with the group that frequently viewed pornographic videos, the group with low-frequency pornography viewing exhibited enhanced functional connectivity in the inferior prefrontal cortex and pars triangularis of Broca’s area in the frontal lobe, the primary somatosensory cortex in the parietal lobe, and the pre-motor and supplementary motor cortices. Moreover, the high-frequency pornography-viewing group exhibited hyperactive parasympathetic activity, more pronounced sexual arousal, and stronger functional connectivity in the dorsolateral prefrontal cortex and frontopolar area. After viewing the pornography, the high-frequency group demonstrated longer reaction times and significantly reduced accuracy while completing the Stroop Color and Word Test (SCWT) compared to the low-frequency group and also their own performance before and after viewing the pornography.DiscussionThis study demonstrated the hyperactive and inhibited brain areas under the impact of pornography video addiction. The results may strengthen our understanding of neurobiology and facilitate the development of prevention policies for adolescents.